Food Pricing at the Prospective Point of View Syariah's Economic Law - Hidayati, Husnul (Spiritus: Religious Studies and Education Journal, 2024)
This study examines how the price adjustment in Labuhan Haji coastal tourist destinations to market conditions. At this location, the charges charged at the tourist sites are higher than the current market prices. Labuhan Haji tourism sets different rates for tourists from outside the area, who have to pay higher than the locals. In this research, the method used is a qualitative method with the type of case study research, and using an empirical approach. Data is collected through observations, interviews, and documentation. Data analysis uses reduction, presentation, and inference on the data collected. Research results show that there is a difference in prices for tourists and local visitors. First, prices are determined by the policies of each trader, who take advantage according to their personal policies. With prices higher than the market price, some buyers feel compelled to buy. Second, in principle, sales should be based on mutual agreement without coercion, and should be done openly and transparently about prices, without discriminating visitor.